2004
DOI: 10.2166/wst.2004.0562
|View full text |Cite
|
Sign up to set email alerts
|

Energy and nutrient recovery from sewage sludge via pyrolysis

Abstract: Energy recovery and nutrient reuse from sewage sludge has traditionally been achieved via anaerobic digestion/power generation with land application of the biosolids. By contrast, thermal processes such as pyrolysis have typically been used only for energy recovery. One such technology has demonstrated at commercial scale that all of the energy in sludge can be beneficially recovered and reused. No attempt was however made to recover and reuse sludge nutrients. There are many potential benefits of using pyroly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
127
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(133 citation statements)
references
References 4 publications
5
127
0
1
Order By: Relevance
“…The relatively high P recovery rate suggested that the P contained in bio-oil or gas was significantly lower than that in biochar. Results are consistent with that of the previous studies where nearly all P forms were recovered from the biochar (Bridle and Pritchard, 2004;Zheng et al, 2013). As pyrolysis progresses, part of oxygen and hydrogen in the feedstock are lost, as well as nitrogen and sulphur, thereby concentrating the remaining P in the biochar (Cantrell et al, 2012;Wang et al, 2012).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The relatively high P recovery rate suggested that the P contained in bio-oil or gas was significantly lower than that in biochar. Results are consistent with that of the previous studies where nearly all P forms were recovered from the biochar (Bridle and Pritchard, 2004;Zheng et al, 2013). As pyrolysis progresses, part of oxygen and hydrogen in the feedstock are lost, as well as nitrogen and sulphur, thereby concentrating the remaining P in the biochar (Cantrell et al, 2012;Wang et al, 2012).…”
Section: Resultssupporting
confidence: 92%
“…These values were significantly reduced compared with 6.4% in MS600, 5.3% in WS600, and 10.9% in PH600. These results are parallel with those obtained from a previous study where pyrolysis at 450°C significantly reduced the water soluble P fraction of N 60% in sewage sludge to b20% in its biochar (Bridle and Pritchard, 2004). Cantrell et al (2012) also reported that the significantly reduced water soluble P in manure biochar is a function of pyrolysis temperature.…”
Section: Chemical Sequential Fractionationsupporting
confidence: 89%
“…Pyrolysis concentrates phosphorus in the char and this can be used as a soil additive or as a concentrated phosphorus source for further extraction and transformation. The former has been developed for treatment of sewage sludge (Bridle and Pritchard, 2004;Viana et al, 2015), however not all the phosphorus is bioavailable (Huang and Tang, 2015). Incineration of manure concentrates phosphorus in the resulting ash.…”
Section: Introductionmentioning
confidence: 99%
“…Inorganic P is concentrated in biochar at temperatures up to 700-8008C (Hossain et al 2011). Commercial-scale pyrolysis plants have been thwarted in the past owing to poor planning but trials have shown agronomically useful nutrient content (Bridle and Pritchard 2004;Wang et al 2012) and that pyrolysis at~5008C stabilised sewage sludge C in soils (Méndez et al 2012). Zhao et al (2013) compared the chemical properties of wastes from a range of feedstocks including municipal waste pyrolysed at 5008C and suggested that those produced from manures and biosolids have slow P-release characteristics.…”
Section: Biochar From Urban Wastementioning
confidence: 99%